Herbicide Safeners Decrease Sensitivity to Herbicides Inhibiting Acetolactate-Synthase and Likely Activate Non-Target-Site-Based Resistance Pathways in the Major Grass Weed Lolium sp. (Rye-Grass) - Duhoux, Arnaud; Pernin, Fanny; Desserre, Diane; Délye, Christophe (Frontiers in Plant Science, 2017)
Herbicides are currently pivotal to control weeds and sustain food security. Herbicides must efficiently kill weeds while being as harmless as possible for crops, even crops taxonomically close to weeds. To increase their selectivity towards crops, some herbicides are sprayed in association with safeners that are bioactive compounds exacerbating herbicide-degrading pathways reputedly specifically in crops. However, exacerbated herbicide metabolism is also a key mechanism underlying evolved non-target-site-based resistance to herbicides (NTSR) in weeds. This raised the issue of a possible role of safeners on NTSR evolution in weeds. We investigated a possible effect of the respective field rates of the two broadly used safeners cloquintocet-mexyl and mefenpyr-diethyl on the sensitivity of the troublesome global weed Lolium sp. (rye-grass) to the major herbicides inhibiting acetolactate-synthase (ALS) pyroxsulam and iodosulfuron+mesosulfuron, respectively. Three Lolium sp. populations were studied in three series of experiments. The first experiment series compared the frequencies of plants surviving application of each herbicide alone or in association with its safener. Safener co-application caused a net increase ranging from 5.0 to 46.5% in the frequency of plants surviving the field rate of their associated herbicide. In a second series of experiments, safener effect was assessed on individual plant sensitivity using vegetative propagation. A reduction in sensitivity to pyroxsulam and to iodosulfuron+mesosulfuron was observed for 44.4 and 11.1% of the plants in co-treatment with cloquintocet-mexyl and mefenpyr-diethyl, respectively. A third series of experiments investigated safener effect on the expression level of 19 Lolium sp. NTSR marker genes. Safeners showed an enhancing effect on the expression level of 10 genes. Overall, we demonstrated that cloquintocet-mexyl and mefenpyr-diethyl both reduced the sensitivity of Lolium sp. to their associated ALS-inhibiting herbicide and most likely exacerbated herbicide-degrading secondary metabolism pathways. This suggests that genetic variation for safener response is present in Lolium sp.. Thus, a possible, uninvestigated way to NTSR evolution could be selection for increased responsiveness to safener action. Delivering safeners exclusively to the crop could mitigate the risk for NTSR evolution in weeds.